Chondrocytes Encapsulation In Hydrogel Beads and Their Response to Polyphosphate Incorporation - Viera Rey, Denis Fabricio (Université d'Ottawa / University of Ottawa, 2020)
In Canada, one in five people suffers from arthritis, of which the most common type is osteoarthritis (OA). OA is a group of joint diseases that cause pain and loss of range of motion and for which there is currently no cure. OA can be caused by numerous factors such as aging, genetics, environmental elements, and abnormal joint biomechanics (e.g., injury, obesity). These diseases are degenerative and lead to the progressive breakdown of joint cartilage, as well as changes in the underlying bone and other tissues of the joint over a period of years to decades. Articular cartilage incorporates a single type of resident cells, termed chondrocyte cells. These cells are entrapped within a dense extracellular matrix that limits their ability to proliferate and migrate to a site of injury, while the absence of blood vessels in the cartilage, amongst other factors, hinders the ability of progenitor cells to reach the site of injury, contributing to a limited capacity for intrinsic regeneration of the damaged tissue following an injury. As such, efforts to develop tissue engineering strategies that combine a biomaterial with bioactive signals to induce cells with the chondrogenic potential to regenerate tissue have been pursued actively. In this thesis, we investigate the potential of one such cartilage tissue engineering approach, whereby chondrocytes are encapsulated with alginate hydrogels incorporating inorganic polyphosphate (polyP), a promising chondrogenic signal. The driving hypothesis of the work was that polyanionic polyP would crosslink within the alginate hydrogel meshwork by ionic bonds with the multivalent cations used to form the hydrogel. Initial efforts focussed on optimizing the sterile chondrocyte encapsulation protocol for alginate beads, chondrocyte culture conditions to reduce proliferation – a response that is associated with dedifferentiation and a pathological state – and protocol for the incorporation of polyP in alginate bead when using calcium as a cationic crosslinker. We observed that polyP release from the calcium-alginate bead exhibited an important burst release to nearly 80% of the initial polyP loading within 24 hours of incubation in the culture medium. Increasing the alginate concentration led to approximately a 2.5-fold increase in polyP retention following the burst release. Subsequent incubation showed a more controlled release for at least 1 week. Efforts to reduce hydrogel swelling and increase its stability by substituting Ca2+ by Sr2+ as a crosslinker did not reduce the release rate during the burst release phase, nor did it increase the polyP retention following this initial stage. Other divalent cations including Mg2+ and Co2+, and pre-loading the polyP-alginate solution with a small concentration of Ca2+ did not impact the release profile either. Chondrocytes encapsulated in calcium- and strontium-alginate beads showed decreased DNA content and increased sulfated glycosaminoglycan accumulation at 1 week when polyP was incorporated in the beads compared to controls without polyP; however, this effect was lost at longer time points. These results suggest that this new material may find applications as a vehicle for the short-term delivery of polyP in joints and other tissues. Further efforts to improve the polyP release profile from alginate beads lead to promising results with the use of polyethylenimine (PEI) as a cationic tethering molecule between polyP and alginate. This thesis aims to generate novel biomaterials that can be used to stimulate cartilage tissue regeneration and to eventually develop a treatment strategy for OA. The work presented here will serve as a basis for continued efforts to ensure the prolonged retention of exogenous polyP into the joint.
Keywords: Cartilage; Tissue Engineering; Osteoarthritis; Alginate beads; Biomaterials; Chondrocytes